FEATURES OF WEEDINESS OF THE FIELD BY ROOT RESIDUES OF CORN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The presence of a large amount of root residues after harvesting corn creates problems for the processing of the field. On the basis of field and laboratory studies, the character of weediness and the main physical and morphological characteristics of rhizomes were revealed. Analysis of the variation curves of the dimensional characteristics of root residues and the mass graphical dependences of rhizomes made it possible to develop a general approach to freeing fields from plant residues of corn.